Guide to the engineering management body of knowledge. (American Society of Mechanical Engineers, 2010)
An authoritative guide to key engineering management principles and practices, this book is divided into eight concise domains of engineering management knowledge, which are further broken down into 46 knowledge areas and 210 sub-knowledge areas. This guide covers a wide range of management topics and practices, including market research, product development, organizational leadership and the management of engineering projects and processes.
Title from PDF title page (ASME eBooks Web site, viewed 12/04/2010).
Keywords: Project management -- Dictionaries.; Project management -- Bibliography.; Technical literature.; elektronické knihy; electronic books